Beginning SQL Queries From Novice to Professional - Churcher, Clare. (Apress : Imprint: Apress, 2008)
Clare Churcher's Beginning SQL Queries is your guide to mastering the lingua franca of the database industry: the SQL language. Good knowledge of SQL is crucial to anyone working with databases, because it is with SQL that you retrieve data, manipulate data, and generate business results. Knowing how to write good queries is the foundation for all work done in SQL, and it is a foundation that Clare lays well in her book. Does not bore with syntax! Helps you learn the underlying concepts involved in querying a database, and from there the syntax is easy Provides exceptionally clear examples and explanations Is academically sound while being practical and approachable.